Power management of hybrid micro-grid system by a generic centralized supervisory control scheme - Ambia, M.; Al-Durra, A.; Caruana, C.; Muyeen, S.M. (2014)
This paper presents a generic centralized supervisory control scheme for the power management of multiple power converters based hybrid micro-grid system. The system consists of wind generators, photovoltaic system, multiple parallel connected power converters, utility grid, ac and dc loads. Power management of the micro-grid is performed under two cases: grid mode and local mode. Central supervisory unit (CSU) generates command signal to ensure the power management during the two modes. In local mode, the dc loads in the ac-dc hybrid system can be controlled. In the case of grid mode operation, power flow between the utility grid and micro-grid is controlled. A novel feature of this paper is the incorporation of the multiple power converters. The generated command signal from the CSU can also control the operation of the multiple power converters in both grid and local modes. An additional feature is the incorporation of sodium sulfur battery energy storage system (NAS BESS) which is used to smooth the output power fluctuation of the wind farm. The effectiveness of the control scheme is also verified using real time load pattern. The simulation is performed in PSCAD/EMTDC.